Paracetamol reduces influenza-induced immunopathology in a mouse model of infection without compromising virus clearance or the generation of protective immunity. Issue 5 (10th February 2011) - Lauder, Sarah N; Taylor, Philip R; Clark, Stephen R; Evans, Rhys L; Hindley, James P; Smart, Kathryn; Leach, Heather; Kidd, Emma J; Broadley, Kenneth J; Jones, Simon A; Wise, Matt P; Godkin, Andrew J; et al.
Abstract : Background: Seasonal influenza A infection affects a significant cohort of the global population annually, resulting in considerable morbidity and mortality. Therapeutic strategies are of limited efficacy, and during a pandemic outbreak would only be available to a minority of the global population. Over-the-counter medicines are routinely taken by individuals suffering from influenza, but few studies have been conducted to determine their effectiveness in reducing pulmonary immunopathology or the influence they exert upon the generation of protective immunity. Methods: A mouse model of influenza infection was utilised to assess the efficacy of paracetamol (acetaminophen) in reducing influenza-induced pathology and to examine whether paracetamol affects generation of protective immunity. Results: Administration (intraperitoneal) of paracetamol significantly decreased the infiltration of inflammatory cells into the airway spaces, reduced pulmonary immunopathology associated with acute infection and improved the overall lung function of mice, without adversely affecting the induction of virus-specific adaptive responses. Mice treated with paracetamol exhibited an ability to resist a second infection with heterologous virus comparable with that of untreated mice. Conclusions: Our results demonstrate that paracetamol dramatically reduces the morbidity associated with influenza but does not compromise the development of adaptive immune responses. Overall, these data support the utility of paracetamol for reducing the clinical symptoms associated with influenza virus infection.